The Influence of Creativity and Entrepreneurial Ability on Business Success: Study on MSMEs located in Binjai City North Sumatra Province - Darma, Aswin Fahmi; Aseandi, Rizki; Munthe, Safaruddin; Azhar, M (JURISMA : Jurnal Riset Bisnis & Manajemen, 2024)
The purpose of this study is to ascertain how innovation and entrepreneurial abilities affect the performance of MSME companies in Binjai City. Researchers discovered that MSMEs are less creative based on observations, and it is nevertheless evident that they lack broad, innovative ideas. Additionally, MSMEs lack the broad insights necessary to create new products, making it challenging for them to succeed as a firm. MSMEs frequently deal with a drop in product production, which causes them to receive profits that fall short of their goals and see an annual dip in revenue. Using primary data sources, this study employs a qualitative research methodology. A questionnaire is used to collect the data. The study's findings support the third hypothesis, which holds that both creativity and entrepreneurial skills simultaneously have significant effects on company success.